Nationalism and political liberty Redlich, Namier, and the crisis of empire - Ng, Amy (Oxford historical monographs., 2004)
Joseph Redlich and Lewis Namier were politically active historians from upper-middle-class assimilated Habsburg Jewish backgrounds. Both devoted their lives to understanding the relationship between political liberty, nationalism, and nationality conflict. In this book, Ng undertakes a comparative analysis of these two men.